Race as an Open Field: Exploring Identity beyond Fixed Choices. Issue 1 (January 2019) - Croll, Paul R.; Gerteis, Joseph
This paper uses new, nationally representative data to examine how Americans describe their own racial and ethnic identities when they are not constrained by conventional fixed categories. Recent work on shifting racial classifications and the fluidity of racial identities in the United States has questioned the subjective and cultural adequacy of fixed categorization schemes. Are traditional racial boundaries breaking down? We explore the possibility in three ways. First, we explore the relationship between open-field identification (asked at time of survey) with fixed-choice racial and ethnic identifications (asked upon panel entry). Despite changes in American racial and ethnic discourse, most people reproduce normative, categorical racial and ethnic descriptors to identify themselves. Yet racial and ethnic classification is more complex and fluid for some respondents, particularly those who had earlier described themselves as Hispanic or mixed race. Second, we investigate the social meaning of alternative racial labels. Within the standard racial and ethnic categories, there are both dominant labels (e.g., White, Black, Hispanic) and less dominant alternatives (e.g., Caucasian, African American, Latinx); in some cases, the differences come with important social distinctions. Third, we explore the ways that a small but important subset of respondents refuse or deny racial identification altogether. We conclude with a discussion of the future of racial and ethnic classifications, paying particular attention to plans for the 2020 U.S. census.